Frontiers in Algorithmics: 12th International Workshop, FAW 2018, Guangzhou, China, May 8-10, 2018, Proceedings - Chen, Jianer; Lu, Pinyan (Lecture Notes in Computer Science, 2018)
This book constitutes the refereed proceedings of the 12th International Workshop on Frontiers in Algorithmics, FAW 2018, held in Guangzhou, China, in May 2018.The 23 full papers presented in this volume were carefully reviewed and selected from 38 submissions. The papers of this workshop provide a focused forum on current trends of research on algorithms, discrete structures, and their applications.